Diffuse and canalicular patterns of glypican‐3 expression reflect malignancy of hepatocellular carcinoma. Issue 3 (6th February 2019) - Kawaida, Miho; Yamazaki, Ken; Tsujikawa, Hanako; Fukuma, Mariko; Abe, Yuta; Kitago, Minoru; Shinoda, Masahiro; Kitagawa, Yuko; Sakamoto, Michiie
Abstract : Glypican‐3 (GPC3) is expressed in most hepatocellular carcinomas (HCCs). To investigate the significance of various GPC3 staining patterns in HCC, we classified 134 HCC patients into three groups: those with diffuse GPC3 staining, canalicular GPC3 staining, and others (including negative staining). HCCs with diffuse staining were correlated with poor differentiation, high Ki‐67 indices, high serum α‐fetoprotein (AFP) levels, and early recurrence. In contrast, HCCs with canalicular staining were well differentiated with lower AFP levels. Overall survival in this group was better than that of the other two groups. Comparative analysis of GPC3 staining patterns with markers for HCC subclassification showed that diffuse staining was correlated with the expression of biliary/stem cell markers, whereas canalicular staining was correlated with expression of the markers of WNT‐activated HCCs. Induction of leucine‐rich repeat‐containing G‐protein‐coupled receptor 5 (LGR5), known as a target of the WNT signaling pathway, in HCC cells resulted in reduced GPC3 expression in vitro . The LGR5‐induced cells formed tumors with canaliculus‐like structures in mice and showed canalicular GPC3 staining. The current findings showed the significance of recognizing distinct GPC3 staining patterns, i.e., diffuse and canalicular, which may reflect different carcinogenetic mechanisms and indicate the level of malignancy of HCC.